A study on the accessibility measures, services and programs offered by the selected academic libraries in Metro Manila to physically handicapped users - Abrigo, Ryan Joseph M. (2010)
This study was conducted to assess the accessibility measures, services and programs of the selected academic libraries in Metro Manila and give necessary recommendations for improvement. Fundamentally, it sought to attain the following: (1) to find out the existing accessibility measures, services and programs offered by the selected academic libraries for their clients with disabilities; (2) to identify certain provisions and guidelines used by the selected academic libraries in providing library and information services to their clients with disabilities; (3) to determine which among the academic libraries have the best accessibility measures, services and programs to offer to physically disabled clients; (4) to formulate appropriate recommendations based on Batas Pambansa Bilang 344, Republic Act 7277 and IFLA Checklist for the enhancement of the accessibility measures and provisions of services and programs in the selected academic libraries. The subjects of this study are chosen based on their experience in handling clients with disabilities.